Tracing the evolution of environmental practices research in the hotel industry: a mixed-review perspective - Christopher Mensah; Edem M. Azila-Gbettor; Divine Tuinese Novieto; George Harrison Coffie; Eric Kodzo Adzivor (Research in Hospitality Management)
The purpose of the study is to map the terrain of extant literature on green hotel practices conducted over 40 decades (1983–2020) and identify the gaps to be addressed by future research. The study examines the content of 561 articles retrieved from the Scopus database. Data generated were analysed using VOSviewer software to reveal research topics represented via keywords, and content analysis to uncover themes and sub-themes in the body of green hotel practices research. The review reveals that research on hotel environmental practices has grown significantly since 2010, with a focus on energy conservation, consumer perceptions and corporate sustainability strategies. However, the field remains fragmented, with most studies being atheoretical, cross-sectional and based on non-probability samples. The study also highlights underexplored areas such as green supply chain management, sustainable leadership and digital sustainability innovations in the hotel industry. Future research should explore emerging themes such as smart technology integration, the role of cultural and regulatory contexts and longitudinal assessments of sustainability impacts. Methodologically, more qualitative and mixed-methods studies are needed to deepen insights into green hotel practices.